Under the same sky (Journal of Parents and Teachers, 2014)
Four hundred years ago, Newton thanked scientists that investigated before him, because this fact made him possible to discover new physic laws. Also, at that same time, Galileo used his telescope for the first time, and thanks to that a new way of looking at astronomy was born. In addition, also at that same time, Kepler published a new treatise about astronomy. We now realise that those scientific advances have evolved until today, but every time we look at the sky we all see the same. The only different thing is the meaning we want to give to it.
Keywords: astronomy; stars; science; international year of astronomy; history of astronomy